External (border) peripheries in Hungary - Baranyi, Béla (Acta Agraria Debreceniensis, 2012)
This study examines the development of external (cross-border) peripheries, as well as the opportunities of catching up in view of the European integration, most specifically the unfolding of the Schengen processes. A conclusion is drawn that the paradigm shift that is to be expected in cross-border relations and the modern, mainly local, small region-based and inter-settlement forms of interregional cooperations could contribute to diminishing the highly unfavourable circumstances from the aspect of rural development and the fostering of the socio-economic cohesion of the Carpathian basin. The new institutionalised legal frameworks of cross-border relations, the EGTCs can successfully promote in the future the acquisition and more efficient use of different development resources, parallel to this the socio-economic catching up of adjacent peripheries, lagging regions on the two sides of the same borders. Above all, they can be important for the utilisation of the direct relations and local resourcesin the Hungarian–Slovak, Hungarian–Ukrainian and Hungarian– Romanian borders along the northeast part of Hungary and for theHungarian–Croatian and Hungarian–Slovene border areas along South Transdanubia.